PENGAJARAN BAHASA ASING DAN TEKNOLOGI INFORMASI: APAKAH ADA PELUANG BAGI PENGAJAR BAHASA QURAN? - Mufidah, Nuril; Abdussalam, Abdulganiy Abimbola; Adebisi, Aliy Abdulwahid (Hunafa: Jurnal Studia Islamika, 2019)
Information Communication Technology (ICT) is one of the globally acknowledged learnings and teaching space today as well as one of the critical propellants of globalization. Development in ICT has vastly transformed every sphere of life and permeated all human actions and endeavors. The influx of ICT is responsible for the e-everything that is now in vogue e-learning, e-mail, e-library, e-registration, e-this, and e-that. This has brought great relief to pedagogy but cannot replace the role played by teachers. However, despite the immense merits of utilizing ICT in teaching, it has been observed that some Arabic language teachers do not make use of such development but stick to the old method of teaching, whereas the language teachers need to incorporate new ideas and technologies into the learning environment to make learning interesting for their students. Based on this premise this paper aims to inform Arabic Language teachers opportunities offered by ICT, used to learning of Arabic. The subjects of the study were students of Arabic Language Education at UIN Maulana Malik Ibrahim Malang Indonesia 2018 academic year and students and Department of Arabic, Faculty of Arts University of Ilorin, Nigeria. The findings of the research are that ICT if adequately harnessed and utilized will go a long way in enhancing the quality of teaching of Arabic, as it was established to teaching other languages of the world.